The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1590/0001-3765202020180757
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional assay Pereskia spp.: unconventional vegetable

Abstract: Pereskia grandifolia Haworth (PGH) and Pereskia aculeata Miller (PAM) are recognized sources of proteins; dietary fiber; vitamins and minerals make this plant leaves, raw, cooked, and braised, an important ally against protein and micronutrient deficiencies. One of the main problems is the presence of antinutritional factors that may interfere in the digestibility and bioavailability of some nutrients. The objective was to evaluate the amino acid profile and the chemical score of the raw leaves and the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…These compounds may be toxic and/or interfere with the digestibility and bioavailability of some nutrients, such as proteins and minerals. In this respect, it is worth mentioning the study in which the amino acid profile of P. aculeata and P. grandifolia leaves was evaluated in addition to the effects of heating media and time on several parameters [66]. These parameters included, among others, the total content of dietary fiber, minerals, oxalic acid, and tannins, and the possibility of trypsin inhibition.…”
Section: Food Product Product Characterization Referencementioning
confidence: 99%
“…These compounds may be toxic and/or interfere with the digestibility and bioavailability of some nutrients, such as proteins and minerals. In this respect, it is worth mentioning the study in which the amino acid profile of P. aculeata and P. grandifolia leaves was evaluated in addition to the effects of heating media and time on several parameters [66]. These parameters included, among others, the total content of dietary fiber, minerals, oxalic acid, and tannins, and the possibility of trypsin inhibition.…”
Section: Food Product Product Characterization Referencementioning
confidence: 99%
“…Os minerais são nutrientes essenciais ao metabolismo e homeostase no corpo humano, logo, a deficiência desses elementos pode resultar em distúrbios e doenças (Gharibzahedi & Jafari, 2017). Assim, alguns estudos comprovaram que tanto a ora-pro-nobis (Santos et al, 2015;Silveira et al, 2020;Tessarini et al, 2021) quanto o xique-xique (Bezerril et al, 2017;Machado et al, 2021) são ricos em minerais. Tal característica pode favorecer a aplicação destas cactáceas no preparo de diversos alimentos e bebidas, podendo ser utilizados como fontes suplementares na dieta humana.…”
Section: Mineraisunclassified
“…Although these leaves are rich in minerals, dietary fiber, antioxidant compounds, and essential amino acids, such as leucine, lysine, and phenylalanine, they also contain antinutritional factors that may decrease the bioavailability and digestibility of some nutrients. Recently, Silveira et al 74 showed that cooking processes reduced total dietary fiber and P and K contents, and drastically decreased the inhibition of trypsin, in comparison to raw Pereskia leaves, suggesting that cooking favors small intestine digestive processes and protein bioaccessibility.…”
Section: The Effect Of Food Processing On the Stability And Bioaccess...mentioning
confidence: 99%
“…Milpa Alta and Atlixco) in boiling water did not affect calcium bioaccessibility. 55 In leaves of the stem-succulent cacti Pereskia aculeata , boiling water treatment was more effective at maintaining the minerals and dietary fiber levels than braising, 74 whereas microwaving led to improved carotenoids extraction and higher antioxidant capacity. 74 Steaming led to higher phenolic content but lower antioxidant activity, and frying promoted the best bioaccessibility but lower recovery of carotenoids.…”
Section: The Effect Of Food Processing On the Stability And Bioaccess...mentioning
confidence: 99%